Effect of Climatic Variations in the Floral Phenology of Berberis microphylla and Its Pollinator Insects - Radice, Silvia; Giordani, Edgardo; Arena, Miriam Elisabet (Horticulturae)
Berberis microphylla (calafate) is an evergreen shrub that grows spontaneously in the Argentinean and Chilean Patagonia with a very harsh climate. This Sub-Antarctic zone is affected by the “El Niño” and “La Niña” pattern, which is measured using the Oceanic Niño Index (ONI). The objective of this study was to analyze the floral phenology and its pollinator insects, in relation to the climatic conditions observed. This work was developed in Ushuaia (Argentina) during 2010, 2014, 2015, and 2016. Significant differences were observed for the development of flower bud and floral phenology between the four years studied. On 26 October, between 84 and 100% of flower buds was recorded in the shrubs tested during the years 2010, 2014, and 2015 and then decreased abruptly in 2010 and more slowly in 2014 and 2015. However, in 2016 on the same date, it was recorded 70% of button flowers increasing to 90% on 5 November and then slowly evolving towards the anthesis phase. On the other hand, the anthesis phase was developed rapidly for 2010 and 2015 and slower for 2014 and 2016. A peak in anthesis occurred on 2 November in 2010, while in the other years, it was observed later in 16 November. The hoverflies of the genus Carposcalis and Allograpta, both insects verified to be responsible for the pollination of calafate, were registered between 2014 and 2016. Carposcalis was significantly more present in 2014, while in 2015 and 2016, Allograpta was predominant. The insect activity was also related with the climatic conditions, i.e., air temperature, air relative humidity, wind speed, and gust of wind along the day during the anthesis phase, and which also modified its life cycle. So, it was observed in 2016, the year with winter temperatures higher than normal, that adult hoverflies ended their hibernation period earlier and began to lay eggs on the juvenile calafate sprouts; hence, the emerging larvae ate the pollen grain of button flowers, causing a decrease in future fruits harvested. The results presented show that the “La ...